Actions to reduce reconciliation differences between received mineral and sent to mill - Herrera Valdez, Johans (2020)
In all mining operations, a reconciliation system is necessary, which allows measuring the performance of the processes involved in obtaining the final product, from the reserve-resource models, through mine design, mine planning, mining production, until culminating in the metallurgical process. It is through the relationship between the ore received (ground ore) with the ore sent to grinding (short-term model), that reconciliation factors will result for tonnage, grade and metal. Subsequently, they will be evaluated in a monthly, quarterly and / or annual period of time, and will help to refine the processes and sub-processes of the short-term model, as well as the mining process and the metallurgical process. The results will be reflected in the reduction of the differences in the reconciliation factors for tonnage, grade and metal, this reduction must be supported over time; In other words, a mining reconciliation system must be part of continuous improvement throughout the value chain of the mining process.